2020
DOI: 10.3390/fermentation6010027
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of β-galactosidase Production by Batch Cultures of Lactobacillus leichmannii 313 (ATCC 7830™)

Abstract: The endoenzyme β-galactosidase (β-d-galactoside galactohydrolase; EC 3.2.1.23) has been used at industrial scales for the preparation of lactose-free milk and for the conversion of lactose to galacto-oligosaccharides (GOS) prebiotics. In this study, using Plackett-Burman (PB) design and the response surface methodology (RSM), the batch growth conditions for the production of β-galactosidase in DeMan-Rogosa-Sharpe (MRS) media have been studied and optimized for Lactobacillus leichmannii 313 (ATCC 7830™) for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 55 publications
3
6
0
Order By: Relevance
“…Hwang found that the growth of BGN4 reached the early stationary phase at that time [ 19 ]. This result is consistent with previous studies indicating that the Fe-dependent SOD activity of a recombinant Pseudomonas putida strain was high in the log-growth and stationary phases of bacterial cells grown in a medium supplemented with FeCl 3 [ 20 ] and the β-galactosidase activity of Lactobacillus leichmannii 313 was the highest in the early stationary phase [ 21 ].…”
Section: Resultssupporting
confidence: 93%
“…Hwang found that the growth of BGN4 reached the early stationary phase at that time [ 19 ]. This result is consistent with previous studies indicating that the Fe-dependent SOD activity of a recombinant Pseudomonas putida strain was high in the log-growth and stationary phases of bacterial cells grown in a medium supplemented with FeCl 3 [ 20 ] and the β-galactosidase activity of Lactobacillus leichmannii 313 was the highest in the early stationary phase [ 21 ].…”
Section: Resultssupporting
confidence: 93%
“…The best 1262 (2023) 062018 IOP Publishing doi:10.1088/1755-1315/1262/6/062018 4 carbon source to encourage the growth of the of β-galactosidase. This is due to the fact that lactose, specifically the allolactose isomer, stimulates the lacZ gene's translation by binding to the Lac repressor protein and blocking it from activating the operator region of the lac operon [15]. These findings are consistent with earlier research.…”
Section: Carbon Sources' Impact On the Generation Of B-galactosidasesupporting
confidence: 90%
“…Numerous studies have documented how carbon sources have a significant impact on the synthesis of -galactosidase by different bacteria. Conclusion: Depending on the microorganisms utilized, the importance of carbon supply in this biosynthesis may vary significantly [15]. This study investigated a variety of carbohydrates (glucose and lactose) to determine the optimal carbon source and best sugar for -galactosidase production.…”
Section: Carbon Sources' Impact On the Generation Of B-galactosidasementioning
confidence: 99%
“…AI ST Lactose/β-galactosidase CCD pH 7.06 and 15.3 g/L lactose [80] An eco-friendly pressure liquid extraction method to recover anthocyanins from broken black bean hulls.…”
Section: Box-behnkenmentioning
confidence: 99%